Emerging infections caused by non-Aspergillus filamentous fungi. (August 2016) - Douglas, A.P.; Chen, S.C.-A.; Slavin, M.A.
Abstract: There are three broad groups of non- Aspergillus moulds: the mucormycetes, the hyalohyphomycetes and the phaeohyphomycetes. Infections with these pathogens are increasingly reported, particularly in the context of increasing use of immunosuppressant agents and improved diagnostics. The epidemiology of non- Aspergillus mould infections varies with geography, climate and level of immunosuppression. Skin and soft-tissue infections are the predominant presentation in the immunocompetent host and pulmonary and other invasive infections in the immunocompromised host. The more common non- Aspergillus moulds include Rhizopus, Mucor, Fusarium and Scedosporium species; however, other emerging pathogens are Rasamsonia and Verruconis species, which are discussed in this article. Outbreaks of non- Aspergillus mould infections have been increasingly reported, with contaminated medical supplies and natural disasters as common sources. Currently culture and other conventional diagnostic methods are the cornerstone of diagnosis. Molecular methods to directly detect and identify mould pathogens in tissue and body fluids are increasingly used.